« La France est, depuis deux siècles, la principale fenêtre vers l’universalité pour les artistes nés en Roumanie ». Entretien avec Matei VIŞNIEC par Iulia MARDAR - MARDAR, Iulia (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
Matei Vișniec studied philosophy in Bucharest, he was a founding member of the Monday Poetry Reading, and asserted himself as a powerful writer even when his plays were prohibited during the communist regime. After 1989, he became one of the most admired Romanian contemporary playwrights. His plays were translated in more than twenty-five languages and are still performed on stages all over the world. He lives in Paris since 1987, and belongs to both Romanian and French literature.